The tongue is fire : South African storytellers and apartheid - Scheub, Harold (ACLS Humanities E-Book., 1996)
In the years between the Sharpeville Massacre of 1960 and the Soweto Uprising of 1976--a period that was both the height of the apartheid system in South Africa and, in retrospect, the beginning of its end--Harold Scheub went to Africa to collect stories.